PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. KALIMIAS BINTANG PRATAMA CABANG LOMBOK TENGAH - Hadi, Khaerul; Hidayah, Baiq Nurul (Valid Jurnal Ilmiah, 2019)
The purpose of this research is to knows the effects of work load variable, work environment and compensation, and to knows the variable that have dominant effects on employee performance in PT. Kalimias Bintang Pratama Branch of Central Lombok. The type of this research is associative research. The population in this research is employees in PT. Kalimias Bintang Pratama Branch of Central Lombok. The quantity of samples that taken was 30 peoples, data collection techniques using questionnaires, and data analysis using multiple linear regression analysis.The results of multiple linear regression analysis show that simultaneously of the three indicators of independent variables significantly have effects of employees performance in PT. Kalimias Bintang Pratama Branch of Central Lombok, Fcount have score greater than Ftable that is 134,032>2,98. In accordance with partial, the workload has a score of t count greater than t table that is3,407>2,055. Work environment has a score ot t count greater than t table that is 7,826>2,055 and compensation has a score of t count greater than t table that is 5,002>2,055.It is positive and significant effects on the performance of employees at PT. Kalimias Bintang Pratama Branch of Central Lombok. And shows that the results of the multiple linear determination coefficient (R2) are 0.939 or 93%. This means that the degree effects of the independent variable (X) on the variable (Y) is 93%.